Sports activities at the fitness center while pandemy COVID-19 in the city of Mataram - Sutawijaya, Lalu Danang; Sugiyanto, Sugiyanto; Riyadi, Slamet (Quality in Sport, 2020)
This study aims to determine the phenomena, motives, and benefits of sports activities at the physical fitness center during the COVID-19 pandemic in the city of Mataram. This type of research is a qualitative research with a phenomenological approach. The technique of taking informants uses the Snowball Sampling technique. Data collection techniques using observation, interviews, and document analysis. The data validity technique uses two triangulation techniques, namely data triangulation and method triangulation. Data analysis was carried out in four stages, namely: data collection stage, data reduction stage, data presentation stage, conclusion drawing stage. The results showed that various methods were carried out by each individual to meet all the needs to stay healthy during the COVID-19 pandemic, one of which was by exercising at a fitness center (Fitness Center) because the place was clean as well as sports equipment and the place of exercise was adequate. But it must also adopt a healthy lifestyle and social distancing. The motives of the community to do sports activities during the COVID-19 pandemic are: want to maintain a healthy body, want to get the ideal body, want to tighten the muscles of the body, want to get happiness and recreation. Benefits of sports activities during the COVID-19 pandemic are: burning fat, increasing physical strength, can prevent disease, detoxification, increase metabolism, reduce stress, increase concentration, train breathing. Keywords: Sports Activities, Physical Fitness, COVID-19 pandemic